Fazlur Rahman's Perspective On The Concept Of An Islamic State In The Qur’an - Naura Safira Salsabila Zain; Ihwan Agustono (Al Hikmah: Jurnal Studi Keislaman, 2023)
Political differences between Islamic Traditionalists and Secular Modernists have resulted in massive progress in the landscape of Islamic political thought. This is highlighted by the formation of a third group, which differs from the traditionalist and secular perspectives on Islamic politics. Fazlur Rahman, who established himself as the neo-modernists' spokesperson, is one of the key figures in this category. This study aims to analyze Fazlur Rahman’s view regarding the Islamic concept of the state, seems more inclined to argue that Islam neither commands nor teaches clearly about the constitutional system but acknowledges that there are a number of values and ethics in the Qur'an. Thus, the qualitative method will be employed in this work, along with a historical study approach gleaned from books, journals, and related publications. This study discovered that Fazlur Rahman's idea of an Islamic state seems to be a somewhat flexible formulation, not too stringent given specific circumstances. This type of formulation will avoid differences of opinion among Muslims, which can lead to the non-recognition of friendly countries as Islamic countries due to different visions, both due to differences in theological schools of thought and schools of law, as well as strategies for implementing and fostering them.